Global trends and hotspots in research on acupuncture for neurodegenerative diseases over the last decade: a bibliometric and visualization analysis - Tan, Qian; Liu, Xinyuan; Xu, Shuyu; Chen, Jiangmin; Li, Weixian; Zhang, Shuai; Du, Yanjun (Frontiers in Aging Neuroscience, 2024)
The purpose of this study was to explore the current status and trends of acupuncture for neurodegenerative diseases (NDs) in the last decade and provide new insights for researchers in future studies.: The publications concerning acupuncture treatment for NDs published between 2014 and 2023 were extracted from the Web of Science Core Collection. We used CiteSpace and VOSviewer to analyze data on numbers of annual publications, countries, institutions, cited journals, cited authors, cited references, keywords, and citation bursts about acupuncture for NDs. Results: A total of 635 publications were obtained from 2014 to 2023. We identified the most prolific journals, countries, institutions, authors, patterns of authorship, and the main direction of future research in the field of acupuncture for NDs in the last decade. The China (389 articles), Beijing University of Chinese Medicine (56 articles), and Evidence Based Complementary and Alternative Medicine (42 articles) were the country, institution, and journal with the most publications,respectively. The high-frequency keywords focused on "alzheimers disease", "parkinsons disease", "acupuncture", "dementia", and "electroacupuncture". The top five keywords in terms of centrality were "cerebral ischemia " , " acupuncture stimulation", "fMRI", "apoptosis", and "deep brain stimulation".The results from this bibliometric study provide insight into the research trends in acupuncture therapy for NDs, and the current status and trends of the past decade, which may help researchers confirm the current status, hotspots, and frontier trends in this field.